Investigating the effects of testosterone on uterine fluid regulation and endometrial receptivity in a rat model / Mohd Helmy Mokhtar - Mohd Helmy , Mokhtar (2016)
Normal regulation of uterine fluid volume, its ionic compositions and normal development of uterine receptivity are important factors that determine successful embryo implantation. The female sex hormones i.e. oestrogen and progesterone, are essential for the reproductive events, including sperm transport, capacitation, fertilization, embryo transport and implantation. In females, testosterone is produced in a very low amount by the ovaries and adrenal glands and is required for some of the normal physiological processes in the uterus. However, when present at the supra-physiological levels, such as in the pathological conditions examples polycystic ovarian disease and in excessive anabolic steroid intakes, the effects of this hormone may be detrimental for some of the physiological processes in the uterus. Up-to-date, effects of supra-physiological levels of testosterone on the regulation of uterine fluid and uterine receptivity have not been fully revealed. We hypothesized that supra-physiological levels of testosterone can affect these uterine parameters, thus could adversely affect the reproductive processes, which could compromise fertility. In this study, we have revealed that testosterone administration to ovariectomised rats, with or without 17β-estradiol decreased the uterine luminal fluid volume, chloride concentrations and cAMP levels and down-regulated CFTR expression but significantly enhanced the expression of Aqp-1, 5 and 7 in the uterus (p<0.05 when compared to in the absence of testosterone). Similarly, supra-physiological testosterone administration in sex-steroid replaced ovariectomised rats mimicking hormonal changes in early pregnancy reduced the pinopode development and MECA-79 expression, decreased the complexity of endometrial tight junction and down-regulated the expression of tight junction proteins i.e. claudin-4 and occludin. Additionally, the expression of αvβ3 integrin, E-cadherin and Muc-1 were also significantly reduced. The effects of testosterone in sex-steroid replaced ovariectomised rats were found to be mediated via the androgen receptor iv however did not involve the active testosterone metabolites, DHT. Meanwhile, in the intact rats, testosterone administration from day 1 to day 3 of pregnancy suppressed pinopodes development, reduced the complexity of endometrial tight junctions and expressions of MECA-79, claudin-4, occludin, αvβ3 integrin, E-cadherin, Muc-1, Msx-1, Fgf-1 and Ihh proteins. Testosterone also reduced the number of embryo implantation. In conclusions, high levels of testosterone could adversely affect the female fertility via altering the normal regulation of uterine fluid volume, its chloride concentration as well as suppresses the endometrial receptivity development. These effects could suppress fertility.